USE OF OSMOTIC TENSIOMETERS IN THE DETERMINATION OF SOIL-WATER CHARACTERISTIC CURVES - Liu, Hengshuo; Rahardjo, Harianto; Satyanaga, Alfrendo; Du, Hejun (Engineering Geology, 2022)
Soil-water characteristic curve (SWCC) correlates the water content of a soil to its soil suction, which is a very important property of unsaturated soils. Osmotic tensiometers (OTs) have shown their capability in high soil suction measurement. This study tried to use OT combined with a pressure plate and WP4C dewpoint potentiometer to determine the SWCC of a residual soil. Three OTs with different measuring ranges (900 kPa, 1200 kPa, 2300 kPa) were prepared for soil suction measurement. The temperature effect on the pressure variations of OTs was illustrated based on Flory-Huggins polymer theories and an appropriate calibration equation was proposed to eliminate the temperature effect on the accuracy of soil suction measurement using OT. The OT showed a fast response in soil suction measurement and the equilibrium can be established in 10–15 min during SWCC measurement. Comparison of the SWCC data obtained from the pressure plate, OT, and WP4C dewpoint potentiometer proves that the OT had good performance in the determination of SWCC, especially for the transition zone (i.e., 10–1500 kPa suction range), by providing more data points to define the SWCC in a shorter period. The results show that the usage of OT will shorten the time required for the determination of SWCC and could be considered as a new and reliable technique in SWCC measurement.
Keywords: Type of access: Open Access; Osmotic tensiometer; High suction measurement; Temperature calibration; Flory-Huggins polymer theories; Soil-water characteristic curve